EFEK DARI BEBAN KERJA, SUASANA KERJA DAN INTERAKSI SOSIAL PADA PRESTASI KERJA SERTA KEMANTAPAN KERJA VARIABEL INTERVENING DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN KUDUS - Aditya Angger Wibowo (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study aims to analyse the effects of workload, work atmosphere, and social interaction on work performance and job stability as intervening variables. To collect data, quantitative analysis was conducted on weighted questionnaires; the validity and reliability of the questionnaires were calculated; and data were collected from independent variables and mediating variables that support them. For estimation and interpretation of results, determining the sample size is crucial, particularly in the context of Structural Equation Modelling (SEM) study. 140 people made up the study's sample size, which employed 27 indicators. The following are the findings of the analysis carried out with Structural Equation Modelling (SEM): Workload significantly and negatively affects job stability. Job stability is positively and significantly impacted by the workplace. Social interaction has a positive and significant effect on job stability. Workload has a negative and significant effect on job performance. Work environment has a positive and significant effect on work performance. Social interaction has a positive and significant effect on work performance. Work performance is positively and significantly impacted by job stability. Job stability can operate as an intermediary between social interaction and job performance, but it cannot act as an intermediary between workload and work environment on work performance.